A porous Ti-based metal–organic framework for CO2 photoreduction and imidazole-dependent anhydrous proton conduction. Issue 8 (9th January 2023) - Qu, Jian-Xin; Fu, Yao-Mei; Meng, Xing; He, Yu-Ou; Sun, Hong-Xu; Yang, Rui-gang; Wang, Hai-Ning; Su, Zhong-Min
Abstract : A porous metal–organic framework for imidazole-dependent anhydrous proton conduction and photocatalytic CO2 reduction. Abstract : The anhydrous proton conductivity of Im@IEF-11 resulting from the integration of imidazole and porous IEF-11 has been investigated, and the highest proton conductive value can reach up to 7.64 × 10 −2 S cm −1 . Furthermore, IEF-11 is also developed to reduce CO2 due to its reasonable structure and suitable energy band, and its CO formation rate is 31.86 μmol g −1 h −1 .